(untitled) (Journal of Global Accounting, 2024)
This study assessed the effect of effluent disclosure on market value added of listed industrial goods firms in Nigeria for a twelve (12) year period covering from 2012-2023. Ex-Post facto research design was employed. Twelve (12) listed industrial goods firms constituted the sample size of this study. Secondary data were extracted from the annual reports and accounts and sustainability reports of the sampled firms and were analysed using E-Views 10.0 statistical software. The study employed inferential statistics using Panel Least Square (PLS) regression analysis. Findings from the empirical analysis showed that effluent disclosure (β1= 0.164494; p-value = 0.000000) has a significant and positive effect on market value added of listed industrial goods firms in Nigeria at 5% level of significance. The study recommended that corporate organizations should ensure that they get ahead of regulation by preparing their businesses for likely mandatory environmental reporting rules, thereby gaining competitive edge when it comes to performance on the stock market, access to capital and winning tenders